TA’ARUF ONLINE MELALUI MEDIA SOSIAL PRESPEKTIF FIKIH MUNAHAKAT - Dhiya, Indi Laela; Falakha, Nadia; Hami, Widodo (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2024)
In the current era of globalization, it causes rapid development and influences the process of finding someone's soul mate. This causes some people to have the mindset of taking advantage of this to look for potential partners, which is done online. Online ta'aruf via social media has become a significant contemporary phenomenon in the process of marriage. This research explores the views of Islamic law regarding the practice of online ta'aruf with a focus on halal, ethical aspects and the concept of marriage in Islam through Islamic legal analysis and literature study. The results of this research indicate that online ta'aruf can be seen as a positive tool in Islam as a means of finding a life partner and getting to know potential partners. However, halal aspects, including fulfilling marriage requirements and compliance with religious norms in the practice of online ta'aruf still need special attention within the framework of the Islamic religion. This research provides a basis for further understanding of Islamic law's view of online ta'aruf via social media in accordance with Islamic religious principles, thereby maintaining the integrity of the marriage process in a digital context